2013
DOI: 10.1002/app.39213
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinylidene fluoride)–acrylic rubber partially miscible blends: Phase behavior and its effects on the mechanical properties

Abstract: A phase diagram of poly(vinylidene fluoride) (PVDF) and acrylic rubber (ACM) was plotted, and the effects of the extent of miscibility on the mechanical properties of the polymer blends were examined. A compressible, regular solution model was used to forecast the phase diagram of this blend. The model prediction, the lower critical solution temperature (LCST) over the upper critical solution temperature (UCST), was done qualitatively according to the experimentally determined phase diagram by differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…In our previous studies [20][21][22][23], we found that the neat PVDF, and the miscible composites of PVDF/ACM blends form a polymorph and PVDF/Clay nanocomposite induce both b and c polymorphs. To study the crystalline structure of PVDF in partially miscible hybrid of PVDF/ACM/Clay, we conducted further XRD analysis.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In our previous studies [20][21][22][23], we found that the neat PVDF, and the miscible composites of PVDF/ACM blends form a polymorph and PVDF/Clay nanocomposite induce both b and c polymorphs. To study the crystalline structure of PVDF in partially miscible hybrid of PVDF/ACM/Clay, we conducted further XRD analysis.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, PVDF/ACM blends have been studied [11,[17][18][19][20][21][22]. In our earlier papers [20][21][22], we have investigated various aspects of miscibility and crystallization behaviors for PVDF and ACM systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is widely used in the literature [11][12][13][14][15][16][17][18][19][20][21][22][23]. However, results obtained from the kinetic approach are controversial.…”
Section: Introductionmentioning
confidence: 96%
“…In our previous paper, miscibility of this blend has been investigated [20,21] by plotting the phase diagram of this blend, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%